2022
DOI: 10.3389/fnut.2022.961182
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Polysaccharide From Chuanminshen violaceum and Its Protective Effect Against Myocardial Injury

Abstract: We isolated and purified a novel polysaccharide from the root of Chuanminshen violaceum, namely, Chuanminshen violaceumis polysaccharide (CVP) and confirmed its structure and molecular weight. Furthermore, in vivo experiment, CVP’s protective effect against myocardial ischemia-reperfusion (I/R) injury in mice was evidenced by significantly reducing I/R-induced myocardial infarction (MI) size, decreasing the secretion of heart damage biomarkers, and improving cardiac function. Then, the myocardial anoxia/reoxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Therefore, decreasing ROS levels and suppressing the secretion of inflammatory cytokines are also critical elements for diabetic wound treatment. Recently, some studies demonstrated that introducing bioactive compounds into the electrospun nanofibers that can enhance the anti-inflammatory and anti-oxidant functions of electrospinning-based dressings seems to be a potentially effective route for diabetic wound treatment [ 26 , 27 ]. Philip et al demonstrated that the electrospinning dressing loaded with growth factor TGF-β helped to recruit inflammatory cells to the wound site, deactivated the superoxide ions, and promoted granulation tissue formation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, decreasing ROS levels and suppressing the secretion of inflammatory cytokines are also critical elements for diabetic wound treatment. Recently, some studies demonstrated that introducing bioactive compounds into the electrospun nanofibers that can enhance the anti-inflammatory and anti-oxidant functions of electrospinning-based dressings seems to be a potentially effective route for diabetic wound treatment [ 26 , 27 ]. Philip et al demonstrated that the electrospinning dressing loaded with growth factor TGF-β helped to recruit inflammatory cells to the wound site, deactivated the superoxide ions, and promoted granulation tissue formation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%